2014
DOI: 10.1111/jcc4.12044
|View full text |Cite
|
Sign up to set email alerts
|

eHealth and Health Literacy: A Research Methodology Review

Abstract: The development of e-health may provide powerful tools to improve health, but users' health literacy plays a role in their abilityThe Internet has provided a powerful platform for changing the way people deal with health issues. More than three-quarters of Americans now have access to the Internet, with up to 80% of them having used the platform to acquire health information (Kuehn, 2011). Health information provided via the Internet can range from educational interventions (Glasgow et al., 2011), to online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 22 publications
(20 reference statements)
3
51
0
2
Order By: Relevance
“…[37] Another study also showed that older adults were less likely than younger adults to value the importance of Patient Health Records (PHRs). [31] There might be several reasons behind these findings including: a) greater ease of use and comfort with technology among younger adults, [38] b) poor usability, availability, and accessibility of HIT functions tailored to the elderly, [39][40][41] c) lower health literacy in the elderly, [42,43] d) lower educational attainment and income in the elderly, [3,44] and e) unique challenges from having chronic diseases that are more prevalent in the elderly that impede use of technology (e.g. arthritis, vision impairment etc.).…”
Section: Discussionmentioning
confidence: 99%
“…[37] Another study also showed that older adults were less likely than younger adults to value the importance of Patient Health Records (PHRs). [31] There might be several reasons behind these findings including: a) greater ease of use and comfort with technology among younger adults, [38] b) poor usability, availability, and accessibility of HIT functions tailored to the elderly, [39][40][41] c) lower health literacy in the elderly, [42,43] d) lower educational attainment and income in the elderly, [3,44] and e) unique challenges from having chronic diseases that are more prevalent in the elderly that impede use of technology (e.g. arthritis, vision impairment etc.).…”
Section: Discussionmentioning
confidence: 99%
“…External links to reputable healthcare websites were recommended as well as the option to view videos about the topic within the application. Portugal (2005Portugal ( /2013 Given the commonly cited barriers of an unclear role, time, and financial burden, the potential of e-health to reach men, bridge the mentioned gap, and motivate them to be more involved in prenatal health is promising (Mackert et al, 2014). E-health can educate difficult-toreach audiences, such as men, and to tailor information in ways that could resonate better than existing programs designed predominantly for women.…”
Section: There Is Also a Vision Somehow Ideologically And Culturally mentioning
confidence: 99%
“…Additional perceived barriers for men being involved in prenatal health include having to work (no time) and the expense of classes or programs (Mackert et al, 2014;Widarsson et al, 2012).…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms have been suggested in the literature (Meppelink, Smit, Buurman, & Van Weert, 2015;Von Wagner, Semmler, Good, & Wardle, 2009;Wilson & Wolf, 2009) but have not, to our knowledge, been tested empirically or in combination. Through this testing, our article responds to the call for theory-driven studies on health literacy and e-health (Mackert, Champlin, Holton, Muñoz, & Damásio, 2014) and adds to the body of European health literacy studies, which is currently limited (Barry, D'Eath, & Sixsmith, 2013).…”
mentioning
confidence: 99%